Early-age microstructure and hydrothermal-aged bond performance at glass fiber reinforced polymer (GFRP) bar - seawater sea-sand concrete (SWSSC) interface - Ke, Linyuwen; Wang, Peng; Leung, Christopher K.Y. (Construction & building materials, 2024)
With escalating demand for concrete and associated burden on natural resources, seawater sea-sand concrete (SWSSC) has been proposed as a sustainable alternative to normal concrete (NC). With the implementation of SWSSC, glass fiber reinforced polymer (GFRP) bar is considered as a promising replacement to conventional steel reinforcements to address the chloride-induced corrosion issue. This study comprehensively investigates the bond strength of GFRP bars embedded in either NC or SWSSC with normal-strength (grade C55) and high-strength (grade C80) mix designs. Moreover, early-age microstructure (including heat flow, micromorphology, components, and pore structure) and mechanical properties (including compressive strength and Young’s modulus) of concrete matrix are analyzed in depth to uncover the load transfer mechanism at the GFRP-concrete interface. Results indicate that saline contents in SWSSC lead to a notably denser microstructure and higher early-age GFRP-concrete bond strength compared to NC for the normal-strength mixes (i.e., 15.5% increase in bond strength with 28-day curing), while such increase is limited for the high-strength groups (i.e., 3.2% increase). Furthermore, no significant decline in the long-term bond performance is observed under accelerated hydrothermal aging conditions. Also, experimental results are employed to evaluate the relationship between bond strength and concrete compressive strength as stipulated in the ACI design guideline, yielding pertinent recommendations for potential enhancements. •Behaviour and durability of GFRP-SWSSC bond was comprehensively investigated.•Various parameters (concrete type and grade, bar size, etc.) were considered.•Mechanical and microstructural tests were performed for possible correlations.•Assessment of existing design guideline was carried out with relevant suggestions.•The results are useful for wider application of GFRP in engineering practice.